Discourse Style in Assyrian Letters during the First Millennium BC (The International Journal of Educational Sciences and Arts, 2024)
Since the earliest known historical period in Mesopotamian civilization, messages and correspondence written on clay tablets with special shapes, known in the Akkadian language as šipirtu or egirtu, represented one of the most prominent channels of communication and interaction that were active between individuals in transferring information and exchanging ideas and opinions, crossing over time and space. We are talking about an important and unique historical era in the history of this civilization, which is the Neo-Assyrian period (911-612 BC). It represented the preparation of official letters for the employees of the Assyrian Kingdom, as well as the letters of its kings, which were revealed by the results of the British Museum’s excavations from the late nineteenth century and the twentieth century (1850- 1905 AD) at the hill Quynjaq in Nineveh, within two sites: the first is the southwestern palace of King Sennacherib and the other is the northern palace, which number more than three thousand letters dating back to the late eighth century BC until the middle of the seventh century BC (716-645 BC), in addition to Other letters from the city of Nimrud (Kalhu) are of great importance and an inexhaustible resource in the study of the history of Assyria, not only because they represent a reflection of the system of administrative work and the development of the communications system in his vast kingdom, but they were also a mirror of the economic, political and social reality that this kingdom experienced in a prosperous period. It controlled half of the ancient world at that time, without being tampered with or subject to certain considerations that would affect its credibility. Based on that vision and the importance that these texts embodied and the scope for study and analysis, our goal in this research was to focus on a linguistic and rhetorical aspect represented by the style of discourse and the approach that was followed in organizing these messages by examining the types of these messages and knowing what each type carried. The ideas and meanings of these messages were undoubtedly reflected in the nature of the context and the choice of methods that take into account the situation and the artic.
Keywords: Discourse Style; Administrative Discourse; Types of Assyrian Letters; Assyrian Royal Letters; Administrative Letters; Assyrian Diplomatic Relations